Economic growth and convergence in the Baltic states: Caught in a middle-income trap? - Karsten Staehr (Intereconomics, 2015)
The Baltic states experienced strong economic growth and a rapid closing of the income gap with developed economies until the onset of the global fi nancial crisis. Since then they have seen a marked slowdown of economic growth. This raises the issue of whether the Baltic states might become caught in a middle-income trap with modest growth and slow convergence. Such a trap may stem from a lack of coordination among different actors in the economy, holding back the growth of productive capacity. Based on the results of empirical studies, it is argued that a middle-income trap cannot be ruled out for the Baltic states given their deep crises, weaknesses in education, simple production and export contents, institutional constraints, and rapidly ageing populations. Policymakers may seek to facilitate faster and more stable growth by taking measures that address a number of structural coordination problems in the Baltic states.
Keywords: 330; Wirtschaftswachstum; Wirtschaftliche Konvergenz; Produktivitätsentwicklung; Baltische Staaten